Pengaruh Kebijakan Deviden dan Profitabilitas terhadap Return Saham pada Perusahaan Perdagangan, Jasa, dan Investasi - Ariani, Imelza; Mulyani, Sri; Sopian, Sopian; Nuridah, Siti (Innovative: Journal Of Social Science Research, 2023)
This research aims to analyze the influence of dividend policy and profitability on stock returns in trading, service and investment companies in the advertising, printing and equipment sub-sectors listed on the Indonesia Stock Exchange in 2020-2022. This research uses independent variables, namely dividend policy and profitability, as well as a dependent variable, namely stock returns. The sampling technique uses purposive sampling. Of the 24 advertising, printing and equipment sector companies listed on the Indonesia Stock Exchange during the research period, only 19 companies met the research criteria. The data analysis used is in the form of quantitative analysis, descriptive analysis, and classical assumption tests. Based on the research results, it shows that the two independent variables dividend policy has no influence on stock returns, nor does profitability have any influence on stock returns.